Palm oil by-product as an alternative feedstuff in Central Kalimantan: 2. The effect of feeding palm oil mill effluent on cholesterol, fatty acid and vitamin A of broilers - Ermin Widjaja; Bambang Ngaji Utomo (Indonesian Center for Animal Research and Development (ICARD), 2007)
Solid heavy paste, a byproduct of crude palm oil processing, is found in an excessive amount in Central Kalimantan. It is estimated that 400 tons of this material were produced per day by crude palm oil (CPO) factories in this region. This material contains 12.63-17.41% crude protein, 9.98-25.79% crude fiber, 7.12-15.15% crude fat, 3217-3454 kcal/kg (gross energy) and 1.5% CPO. Considering its composition, this material can be used as an ingridient in broiler’s diet. This study was conducted on broiler chickens of Hubbard strain in Kapuas district. The objectives of the experiment were to study the cholesterol, fatty acid and vitamin A retained in meat and liver of broilers as a result of feeding ration containing solid heavy paste. This experiment was arranged in a completely randomized design. The treatments were levels of solid in the diet, i.e., 0.0, 12.5, 25 and 37.5%. Four hundred broilers were divided into 4 treatmen groups with 5 replications, consisted of 20 chickens in each replication. Data was analyzed based on statistical and descriptive analyses. The results of this experiment indicated that 25% solid in the diet decreased the total fat and cholesterol in the meat and liver, but increased polyunsaturated fatty acid contained in meat. The highest contain of vitamin A in meat and liver was found in the group that received diet containing 12.5% solid. Key Words: Solid, Broiler Chickens, Cholesterol, Fatty Acid, Vitamin A